Conduct followed in a patient suffering from giant condyloma acuminatum in the perianal region - Eneldo Lázaro Arcas Nápoles; Nildé-Líz Vasallo Hernández (Acta Médica del Centro, 2013)
The case of a male patient suffering from a giant condyloma acuminatum in the perianal region is reported. The patient was referred to the Proctological Surgery Consultation. The therapeutic method used was the total resection of de tumor. A meticulous coagulation was applied over the entire area. The surgical wound was left open for closure by secondary intent. The jumping goat position or open razor was chosen, and the entire tumor was removed. At the end of postoperative follow-up period the patient was discharged with a satisfactory outcome.